A longitudinal study of early pretense: Metarepresentational or not. (July 2021) - Kim, Sunae; Kristen-Antonow, Susanne; Sodian, Beate
The metarepresentational aspect of early pretend play (make-believe activities where children create or participate in creating a new situation different from a real one) has been theoretically debated. In the present longitudinal study of N = 83 children, we tested for predictive relations of shared attention at 12–18 months, implicit false belief (FB) at 18 months, and pretend production at 18 months, as well as comprehension at 24 months. We also tested for long-term predictive relations of pretense production and comprehension with theory of mind (ToM) at the age of 4–5 years. Only pretense production directed toward others (but not self) was specifically related to infancy measures of shared attention. Early pretense, either production or comprehension, was not related to implicit FB or later ToM measures. The findings are discussed in terms of different theoretical accounts of early pretense.